The review of Extensible Authentication Protocol and its methods - Nikeshin, A.V.; Shnitman, V.Z. (Trudy Instituta sistemnogo programmirovaniâ, 2018)
Authentication is associated with a scenario, in which some party (the applicant) presented the identity of the principal and states that this is the principal. Authentication allows some other party (verifier) to make sure that this statement is legitimate. Authentication is widely used in access control systems to networks and resources of computing systems. In this context, of considerable interest is the Extensible Authentication Protocol (EAP), specified by the IETF in RFC 3748, which provides an effective mechanism for embedding various authentication methods into it, as well as the proper methods of EAP authentication, some of which were standardized in specifications IETF. This article is a review of Extensible Authentication Protocol (EAP) and its methods, specified by IETF. EAP provide an effective flexible authentication mechanism that can be easily expanded with new authentication methods. The variety of mechanisms used to implement the authentication service are shown. The work was performed under support of the Russian Foundation for Basic Research, research grant № 16-07-00603 "The verification of security functionality of the EAP authentication protocol and evaluation of the robustness of its implementations against attacks".